新加坡华语口语中“然后”与"then"之语用功能 = The pragmatic functions of Ranhou and then in Singapore spoken Chinese - 符凯琪 Foo, Kai Qi (2015)
语言是人类无法缺少的交际工具。世界上的任何一种语言都会随着所接触到的社会环境而有所改变。新加坡是一个多文化多语言国家，新加坡华语也逐渐形成具有本土特色的语言。本研究以“然后”和 then 为例，探讨他们在新 加坡华语口语的扩展语用功能。根据前人研究，“然后”一词在现代汉语口语中的语用功能有所增加，然而针对新加坡华语口语中“然后”的探讨极少。因此，本文使用新加坡华语口语的语料库对“然后”的语用功能进行分析，并观察其与中国普通话里语用功能的异同。笔者发现，“然后”在新加坡华语口语中有作为填补词的功能，这项功能在中国普通话里较为少见。“然后”的英语对应词 then 也经常出现于新加坡华语语境中，因此本研究也在语料库基础上探讨并比较两者在语用功能上的异同。笔者发现 then 在新加坡口语中还可经常用于表达疑问，而“然后”尚不具备该功能。Language is an important communication tool of human beings. Any language in the world will be affected by the social environment it comes into contact with and changes accordingly. In a multi-cultural and multi-language country like Singapore, Singapore Chinese also forms into a language with local characteristics. This study uses ranhou and “then” as examples to explore their increased pragmatic functions in the context of Singapore spoken Chinese. According to previous research, there is a phenomenon of increased pragmatic functions of ranhou in Mainland Chinese, but no such research has been carried out on Singapore spoken Chinese. Therefore, this thesis uses the corpus of spoken Singapore Chinese, and observes for any difference between the pragmatic functions of ranhou in Mainland Chinese and Singapore spoken Chinese. This study finds that ranhou in the latter can be used as a discourse filler, whereas this function was less observed in the China Mandarin context. Then, the corresponding word for ranhou in English, is also frequently used in Singapore Chinese conversation. Therefore, this thesis also analyzes “then” that appears in the corpus and compares the functional differences between “then” and ranhou. It is found that “then” can be used as a question marker, while ranhou does not possess this pragmatic function.